Analisis Sistem Manajemen Keamanan Di Perusahaan Tokopedia Dalam Menigkatkan Proteksi Data Dan Privasi Pengguna - Edy Soesanto; Alfonso Lande; Heru Tian Sanjaya; Muhammad Rafli Hermawan (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
With the increasing use of information technology in various fields, including e-commerce, ensuring user data and privacy protection is crucial for companies like Tokopedia, one of the largest e-commerce companies in Indonesia. This research aims to identify Tokopedia's security management system and its challenges in protecting user data and privacy. The study utilizes a literature review methodology, analyzing various documents, books, and journals related to Tokopedia's security management system. The research objectives are to understand the system's effectiveness, challenges, and Tokopedia's efforts to improve data and privacy protection. Tokopedia has prioritized information security since its establishment, implementing tight security measures, and continuously improving them. Tokopedia Shield, a security feature introduced in 2015, has significantly reduced fraud risk in the platform. Additionally, the company has taken several steps to secure user data, such as data encryption, access restriction, and password quality enhancement. Tokopedia continuously develops its security system, incorporating the latest technologies such as Artificial Intelligence (AI) and Big Data Analytics to detect potential threats early and improve the security system's responsiveness.